Ohmic contact engineering in few–layer black phosphorus: approaching the quantum limit. (29th May 2020) - Telesio, F; le Gal, G; Serrano-Ruiz, M; Prescimone, F; Toffanin, S; Peruzzini, M; Heun, S
Abstract: Achieving good quality Ohmic contacts to van der Waals materials is a challenge, since at the interface between metal and van der Waals material different conditions can occur, ranging from the presence of a large energy barrier between the two materials to the metallization of the layered material below the contacts. In black phosphorus (bP), a further challenge is its high reactivity to oxygen and moisture, since the presence of uncontrolled oxidation can substantially change the behavior of the contacts. Here we study three of the most commonly used metals as contacts to bP, chromium, titanium, and nickel, and investigate their influence on contact resistance against the variability between different flakes and different samples. We investigate the gate dependence of the current–voltage characteristics of field–effect transistors fabricated with these metals on bP, observing good linearity in the accumulation regime for all metals investigated. Using the transfer length method, from an analysis of ten devices, both at room temperature and at low temperature, Ni results to provide the lowest contact resistance to bP and minimum scattering between different devices. Moreover, we observe that our best devices approach the quantum limit for contact resistance both for Ni and for Ti contacts.